Energy efficiency analysis of an integrated glycerin processor for PEM fuel cells: Comparison with an ethanol-based system - Oliva, Diego Gabriel (2010)
The aim of this work is to analyze energetically the use of glycerin as the primary hydrogen source to operate a proton exchange membrane fuel cell. A glycerin processor system based on its steam reforming is described departing from a previous process model developed for ethanol processing. Since about 10% w/w of glycerin is produced as a byproduct when vegetable oils are converted into biodiesel, and due to the later is increasing its production abruptly, a large glycerin excess is expected to oversaturate the market. The reformed stream contains mainly H2 but also CO, CO2, H2O and CH4. As CO is a poison for PEM fuel cell type, a stream purification step is previously required. The purification subsystem consists of two water gas shift reactors and a CO preferential oxidation reactor to reduce the CO levels below 10 ppm. The reforming process is governed by endothermic reactions, requiring thus energy to proceed. Depending on the system operation point, the energy requirements can be fulfilled by burning an extra glycerin amount (to be determined), which is the minimal that meets the energy requirements. In addition a self-sufficient operation region can be distinguished. In this context, the water/glycerin molar ratio, the glycerin steam reformer temperature, the system pressure, and the extra glycerin amount to be burned (if necessary) are the main decision variables subject to analysis. Process variables are calculated simultaneously, updating the composite curves at each iteration to obtain the best possible energy integration of the process. The highest net system efficiency value computed is 38.56% based on the lower heating value, and 34.71% based on the higher heating value. These efficiency values correspond to a pressure of 2 atm, a water/glycerin molar ratio of 5, a glycerin steam reformer temperature of 953 K, and an extra glycerin amount burned of 0.27 mol h-1. Based on the main process variables, suitable system operation zones are identified. As in practice, most PEM fuel cells operate at 3 atm, optimal variable values obtained at this condition are also reported. Finally, some results and aspects on the system performance of both glycerin and ethanol processors operated at 3 atm are compared and discussed.